Medical negligence law in Malaysia - Jahn Kassim, Puteri Nemie (International Law Book Services, 2003)
The medical profession in the recent past has been incresingly confronted with legal issues on negligence alleged to have been caused by doctors, both in private clinics and Government hospitals. The consequence of such medical negligence has created anxious moments to the affected patients as well as the alleged doctors and hospitals.